Self-Regulation in Online Interactions: A Comprehensive Study of Indonesian Tertiary EFL Students and Course Content Amid the Post-Pandemic Era - Arik Eriyanto; Sofendi Sofendi; Machdalena Vianty (STAI Hubbulwathan Duri, 2023)
The transition to online learning during the COVID-19 pandemic presented significant challenges in Indonesia, particularly due to limited facilities and the struggle of students to adapt to independent learning modalities. This study investigates the online learning experiences of students in the English Education Study Program at the University of South Sumatra, with three specific objectives: 1) to assess how students managed their online interactions with learning materials, 2) to identify the challenges faced in these interactions, and 3) to propose solutions to overcome these challenges. Data were collected from a sample of 12 students, four from each of the 3rd, 5th, and 7th semesters, with GPAs between 3.51 and 4.00. A questionnaire was administered via Google Forms and disseminated through a WhatsApp group. Findings indicate that despite being well-prepared and organized, students actively sought to resolve issues they encountered, through methods such as conducting experiments and completing both guided and independent tasks. This study offers insights that may help educators develop strategies to promote self-regulated learning among students.